Transformation of Thanksgiving and Salvation Rituals Ahead of Birth: A Study of Meuri' Tradition in Mandar Society from the Perspective of Urf' - Tualamsyah Wahab, Muh; Mansur, Rahmat (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The study aims to explore and analyze the practice of the Meuri' tradition and its relevance in Islamic law. The main focus of this research is to understand how the Meuri' tradition, as a ritual of gratitude and a plea for safety for the mother and baby approaching childbirth, is applied within the context of Islamic law. This research employs a field research method with normative shari'ah and sociological approaches. The findings indicate that the Meuri' tradition is performed at seven to nine months of pregnancy and includes various rituals such as the recitation of the Barasanji text, communal prayers, and the use of symbols like bananas, free-range chicken eggs, and silk sarongs. The ritual process involves massaging with coconut oil, the use of incense, and predicting the baby's gender with chicken and rice. The ritual concludes with macceraq, which involves applying a mixture of chicken blood and lime to the pregnant woman's forehead and placing a “burabeq” for protection. The study's findings show that the Meuri' tradition not only functions as a form of gratitude and plea for safety but also aligns with the Maqasid al-Shari'ah, which considers the benefits of religion, life, lineage, intellect, and wealth, and plays a role in preserving cultural heritage and community well-being.